China's food economy to the twenty-first century: supply, demand, and trade - Huang, Jikun; Rozelle, Scott; Rosegrant, Mark W. (International Food Policy Research Institute, 1997)
This paper accounts for the structural changes now taking place in China ... and suggests that China is not likely to become either an enormous importer or exporter of grain. Ultimately, though, China's grain balances will depend on decisions made by Chinese policymakers rather than natural resource constraints